Upaya Penyelesaian Hak atas Hki Antara Indonesia dengan Malaysia Terkait Asal Usul Batik dalam Perspektif Hukum Perdata Internasional - Bagus Dewa Maarif; Ema Prastiyanti; Jun Wily Saragih; Karina Diyah Lestari; Noni Prihandini (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Indonesia is a country that has diversity in it. Starting from the diversity of ethnicities, languages, cultures to traditional arts which of course are unique characteristics of the country of Indonesia. One of the arts owned by Indonesia is Batik. Batik as a work of art has become a richness of Indonesian culture which is admired by the general public, both the Indonesian people themselves and the world community, but behind it all, batik is a form of traditional Indonesian art that requires maintenance, preservation and protection so that it can be enjoyed. by the next generation. This is so because batik is one of Indonesia's cultural products that is vulnerable to becoming a victim of recognition from other countries. There are quite a few phenomena that occur where batik is actually recognized or claimed by neighboring countries, such as Malaysia. This research was conducted to determine the chronology of Batik recognized by Malaysia, in addition to knowing the resolution efforts made by the government in terms of protecting Intellectual Property Rights (IPR) as Batik in Indonesia from the perspective of International Civil Law.